Uncatalysed steam pretreatment regimes for bagasse and harvest residues in a sugarcane biorefinery - Hamann, Martin Louis (Stellenbosch : Stellenbosch University, 2021)
ENGLISH ABSTRACT: Biorefining of sugarcane lignocellulosic wastes, i.e. bagasse and harvest residues, at existing cane sugar mills can diversify product ranges to potentially improve profitability. Bagasse is the fibrous residue after juice extraction from the cane and harvest residues are all agricultural wastes generated during sugarcane harvesting. Pretreatment, the first step in bioprocessing of lignocellulose, must ensure maximum yields of desired sugar intermediates (glucose, xylose and arabinose) according to lignocellulosic feedstock and downstream bioconversion requirements. This study chose steam pretreatment for its proven track record in largescale operations and availability of steam at sugar mills, and was studied uncatalysed to allow operation without chemicals addition. The originality of this study firstly included the direct comparison of bagasse and harvest residues pretreatment operability in the same equipment. Uncatalysed steam pretreatment of these feedstocks was optimised by response surface methodology in the ranges of 185 – 215 °C and 5 – 15 min for maximum digestibility (indication of cellulose accessibility to enzymes) of the solids, maximum combined sugar yield (CSY) and maximum hemicellulose recovery to identify preferred pretreatment operating regimes. Secondly, deacetylation (acetyl groups removed from lignocellulose with a mild alkaline extraction) upstream of uncatalysed steam pretreatment was proposed as a detoxification step to remove acetic acid in downstream fermentation. Uncatalysed steam pretreatment of raw and deacetylated bagasse and harvest residues was compared on digestibility, fermentability (portion of maximum theoretical ethanol yield that can be obtained) and dewaterability of the pretreated material. Thirdly, the contribution of the explosion step during steam pretreatment to improving digestibility of the pretreated solids was investigated by comparing material retained and released during the sudden depressurisation at the end of pretreatment. The most significant findings of this study included that sugarcane harvest residues were better suited than bagasse for biorefining via a sugar platform for the following reasons: (1) harvest residues allowed for robust uncatalysed steam pretreatment at a single condition (between 198 and 200 °C, and between 8 and 12 min) to obtain at least 95% of the maximum digestibility, CSY and hemicellulose recovery values, respectively; (2) maximum digestibility was obtained at lower severity (205.8 °C, 8.7 min as opposed to 215 °C, 15 min for bagasse); (3) pretreated harvest residues did not require detoxification at optimum pretreatment conditions; and (4) pretreated harvest residues displayed better dewaterability, especially when pretreated for maximum hemicellulose recovery, compared to bagasse. Furthermore, it was found that the mechanical impingement experienced by steam pretreated material as it is transported during depressurisation, has a significant contribution to improving digestibility. Also, it was found that deacetylation of feedstocks can be performed prior to uncatalysed steam pretreatment as a detoxification step that could potentially increase fermentability of pretreated pressed slurries (not washed). Consequently, it is proposed that bagasse continues to be used to generate steam and electricity in a sugar mill, while attention should be given to the recovery, collection and allocation of sugarcane harvest residues as an attractive sugarcane biorefinery feedstock.